Influence Of Growth Temperature Of PGaN Layer On The Characteristics Of InGaN/GaN Blue Light Emitting Diodes - Asri, R. I. M.; Hamzah, N. A. (2020)
InGaN/GaN blue light-emitting diodes (LEDs) have been successfully growth via metal organic chemical vapor deposition (MOCVD) in temperature range 920 to 1020 °C growth temperatures for p-GaN layer. The significant of p-GaN growth temperature are studied in detail according to the electrical, optical, and structural performances of InGaN/GaN multiple-quantum-well (MQW) blue LEDs. From experimental analysis, decrement growth temperature of p-GaN layer shows improvement trends in term of output power values and turn on voltage values. The optical and structural properties of InGaN/GaN MQW blue LEDs structure were enhanced based on the decrement of photoluminescence (PL) intensity with increasing growth temperature of the p-GaN layer. This study yields an optimized p-GaN layer growth temperature for understanding highly efficient InGaN/GaN blue LED devices.